From face-to-face to online language teaching: The use of technology during the first COVID-19 lockdown - Nikitaki, Stavroula (δ, 2021)
The coronavirus pandemic changed the educational landscape overnight. Face-to-face teaching necessarily shifted to an online delivery of learning, urging teachers to adopt various technology tools, most of which they had never used before, and giving rise to a different approach in teaching. This study aims to map how technology was used in online language teaching during the first COVID-19 lockdown in the Greek educational context. By recording the tools used, the pedagogy underlying their use and the factors that affected the quality of online teaching in this critical period, the study aspires to provide recommendations regarding the effective implementation of technology in online teaching in the future. In this survey, a mixed methods approach was used. Data were collected through an online questionnaire and interviews of language teachers working in Greek Primary Schools during the first COVID-19 lockdown. Although a number of challenges the teachers faced in this unprecedented situation were unveiled, a positive attitude towards the newly acquired knowledge on the use of technology tools was highlighted. At the same time, the need for teacher training and for a closer focus on pedagogy when implementing technology in online teaching was also established.
Keywords: Coronavirus pandemic; Online delivery of learning; Technology tools; t COVID-19 lockdown